1993
DOI: 10.1093/cvr/27.3.423
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac angiotensin receptors in experimental hyperthyroidism in dogs

Abstract: Experimental hyperthyroidism in dogs results in activation of the plasma renin-angiotensin system and up regulation of left ventricular, aortic, and liver angiotensin II receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…These data indicate that factors other than hemodynamic changes play an important role in the pathogenesis of T 4 -induced cardiac hypertrophy [30,31], and clinical evidence suggests that blocking the actions of angiotensin II might confer protective benefits beyond lowering BP [32]. Although there is controversy regarding the formation of myocardial fibrosis induced by TH [33][34][35], considering that RAS is activated in patients with hyperthyroidism [16,17] and myocardial fibrosis depends on a complex relationship between stimulatory (including angiotensin II, endothelin I, catecholamines and aldosterone) and inhibitory factors acting on the collagen production [36], it is reasonable to suggest that these mechanisms could mediate the increased myocardial fibrosis observed in our experimental data, suggesting the involvement of TH in regulating myocardial fibrosis. Interestingly, treatment with RAS inhibitor was presently able to prevent myocardial fibrosis.…”
Section: Hyperthyroidism and Cardiac Functionmentioning
confidence: 97%
See 1 more Smart Citation
“…These data indicate that factors other than hemodynamic changes play an important role in the pathogenesis of T 4 -induced cardiac hypertrophy [30,31], and clinical evidence suggests that blocking the actions of angiotensin II might confer protective benefits beyond lowering BP [32]. Although there is controversy regarding the formation of myocardial fibrosis induced by TH [33][34][35], considering that RAS is activated in patients with hyperthyroidism [16,17] and myocardial fibrosis depends on a complex relationship between stimulatory (including angiotensin II, endothelin I, catecholamines and aldosterone) and inhibitory factors acting on the collagen production [36], it is reasonable to suggest that these mechanisms could mediate the increased myocardial fibrosis observed in our experimental data, suggesting the involvement of TH in regulating myocardial fibrosis. Interestingly, treatment with RAS inhibitor was presently able to prevent myocardial fibrosis.…”
Section: Hyperthyroidism and Cardiac Functionmentioning
confidence: 97%
“…However, there are also conflicting reports regarding the preventative nature of sympathetic inhibition in TH-induced cardiac hypertrophy [12,13]. TH directly stimulates renin mRNA in vivo [13,14] and in vitro [15], and increases both the synthesis and secretion of angiotensinogen and angiotensin (ANG) II receptors [16]. Also, TH activates circulating and tissue RAS without involving the SNS, and this may account for the cardiac hypertrophy observed in hyperthyroidism [14,17].…”
Section: Echocardiographymentioning
confidence: 99%
“…T3 also increased angiotensinogen production from liver in rats 84) . However, another report failed to detect any changes in the angiotensinogen level in the hyperthyroid dog 85) . The differential results may be ascribed to the difference of species or duration and dosages of T3 treatment.…”
Section: Thyroid Hormone and Angiogenesismentioning
confidence: 94%
“…The differential results may be ascribed to the difference of species or duration and dosages of T3 treatment. Interestingly, both studies reported an increase in plasma angiotensin II levels 84,85) , suggesting that the systemic RAS is eventually activated in hyperthyroidism regardless of angiotensinogen levels.…”
Section: Thyroid Hormone and Angiogenesismentioning
confidence: 96%
“…While TH indirectly modifies atherosclerotic risk factors such as lipid profile (2,3) and blood pressure (4), direct effects act via vascular smooth muscle cells, altering vascular tone (5), angiotensin-II type 1 receptor modulating the proliferation of vascular smooth muscle cells (6), upregulation of basic fibroblast growth factor causing enhanced angiogenesis (7), modulating the maturation and functioning of macrophages (8), and acting on the renin-angiotensin system (9,10). However, clinical studies yield conflicting results and mechanistic explanations remain elusive (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%